Answer:
![\displaystyle y=\frac{16-9x^3}{2x^3 - 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B16-9x%5E3%7D%7B2x%5E3%20-%203%7D)
![\displaystyle y=-\frac{56}{13}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D-%5Cfrac%7B56%7D%7B13%7D)
Step-by-step explanation:
<u>Equation Solving</u>
We are given the equation:
![\displaystyle x=\sqrt[3]{\frac{3y+16}{2y+9}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%5Csqrt%5B3%5D%7B%5Cfrac%7B3y%2B16%7D%7B2y%2B9%7D%7D)
i)
To make y as a subject, we need to isolate y, that is, leaving it alone in the left side of the equation, and an expression with no y's to the right side.
We have to make it in steps like follows.
Cube both sides:
![\displaystyle x^3=\left(\sqrt[3]{\frac{3y+16}{2y+9}}\right)^3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E3%3D%5Cleft%28%5Csqrt%5B3%5D%7B%5Cfrac%7B3y%2B16%7D%7B2y%2B9%7D%7D%5Cright%29%5E3)
Simplify the radical with the cube:
![\displaystyle x^3=\frac{3y+16}{2y+9}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E3%3D%5Cfrac%7B3y%2B16%7D%7B2y%2B9%7D)
Multiply by 2y+9
![\displaystyle x^3(2y+9)=\frac{3y+16}{2y+9}(2y+9)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E3%282y%2B9%29%3D%5Cfrac%7B3y%2B16%7D%7B2y%2B9%7D%282y%2B9%29)
Simplify:
![\displaystyle x^3(2y+9)=3y+16](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E3%282y%2B9%29%3D3y%2B16)
Operate the parentheses:
![\displaystyle x^3(2y)+x^3(9)=3y+16](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E3%282y%29%2Bx%5E3%289%29%3D3y%2B16)
![\displaystyle 2x^3y+9x^3=3y+16](https://tex.z-dn.net/?f=%5Cdisplaystyle%202x%5E3y%2B9x%5E3%3D3y%2B16)
Subtract 3y and
:
![\displaystyle 2x^3y - 3y=16-9x^3](https://tex.z-dn.net/?f=%5Cdisplaystyle%202x%5E3y%20-%203y%3D16-9x%5E3)
Factor y out of the left side:
![\displaystyle y(2x^3 - 3)=16-9x^3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%282x%5E3%20-%203%29%3D16-9x%5E3)
Divide by
:
![\mathbf{\displaystyle y=\frac{16-9x^3}{2x^3 - 3}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%5Cdisplaystyle%20y%3D%5Cfrac%7B16-9x%5E3%7D%7B2x%5E3%20-%203%7D%7D)
ii) To find y when x=2, substitute:
![\displaystyle y=\frac{16-9\cdot 2^3}{2\cdot 2^3 - 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B16-9%5Ccdot%202%5E3%7D%7B2%5Ccdot%202%5E3%20-%203%7D)
![\displaystyle y=\frac{16-9\cdot 8}{2\cdot 8 - 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B16-9%5Ccdot%208%7D%7B2%5Ccdot%208%20-%203%7D)
![\displaystyle y=\frac{16-72}{16- 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B16-72%7D%7B16-%203%7D)
![\displaystyle y=\frac{-56}{13}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%5Cfrac%7B-56%7D%7B13%7D)
![\mathbf{\displaystyle y=-\frac{56}{13}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%5Cdisplaystyle%20y%3D-%5Cfrac%7B56%7D%7B13%7D%7D)
Answer:
(x+1)(2x-3)(3x-5)
Step-by-step explanation:
Answer:
kkk
Step-by-step explanation:
kkkkkkhjhj
Answer:
Step-by-step explanation:
Step 1: Convert into improper fractions
Step 2: Find least common denominator and find equivalent fractions
Step 3 : Do the required operation
![3\frac{1}{2}+2\frac{1}{4}-1\frac{1}{2}=\frac{7}{2}+\frac{9}{4}-\frac{3}{2}\\](https://tex.z-dn.net/?f=3%5Cfrac%7B1%7D%7B2%7D%2B2%5Cfrac%7B1%7D%7B4%7D-1%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B7%7D%7B2%7D%2B%5Cfrac%7B9%7D%7B4%7D-%5Cfrac%7B3%7D%7B2%7D%5C%5C)
Least common denominator of 2 , 4 = 4
![=\frac{7*2}{2*2}+\frac{9}{4}-\frac{3*2}{2*2}\\\\=\frac{14}{4}+\frac{9}{4}-\frac{6}{4}\\\\=\frac{14+9-6}{4}\\\\=\frac{17}{4}\\\\=4\frac{1}{4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7%2A2%7D%7B2%2A2%7D%2B%5Cfrac%7B9%7D%7B4%7D-%5Cfrac%7B3%2A2%7D%7B2%2A2%7D%5C%5C%5C%5C%3D%5Cfrac%7B14%7D%7B4%7D%2B%5Cfrac%7B9%7D%7B4%7D-%5Cfrac%7B6%7D%7B4%7D%5C%5C%5C%5C%3D%5Cfrac%7B14%2B9-6%7D%7B4%7D%5C%5C%5C%5C%3D%5Cfrac%7B17%7D%7B4%7D%5C%5C%5C%5C%3D4%5Cfrac%7B1%7D%7B4%7D)
<span>When you round 699,900 to the nearest hundred, you get 700,00.</span>